Production Of Peptone From Waste Beer Industry Using Papain for Bacterial Growth Medium - Rahman .; Dedi Fardiaz; Tami Idiyanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
An experiment was conducted to hydrolyze waste of beer industry using papain to produce peptone. Papain with activity of 691.5 units based on casein substrat was used in this experiment. Results showed that optimum conditions for hydrolysis processes were as follows : substrate concentration 3.2%, papain concentration 0.4%, temperature 60-70OC, pH 6.0, hydrolysis time 5 hours. With 5 liter fermentation jar as much as 3.8 liter of hydrolyzate could be produced with 19.23% of peptone. The resulting peptone had the following characteristics : solubility 90.7%, N-amino 3.25%, N-total 11.23%, protein 70.19%, water 5.5% and ash 7.9%. This peptone gave the same effectivity for bacterial growth as that fron commercial Bacto peptone and Yeast extract to support the bacterial growth. Key words : Peptone, waste of beer industry, papain, bacterial growth medium.